Do aluminum (Al)-accumulating species from the Brazilian savanna accumulate Al in the roots? - Zaia, Marina [UNESP]; Timpone, Luá Taibo [UNESP]; Habermann, Gustavo [UNESP] (Springer Nature, 2022)
Key message: Al-accumulating species are tolerant, accumulating more than 1000 mg Al kg−1 dry leaves, and varying root Al concentrations. Non-accumulating species are ‘avoiders’, retaining low root and leaf Al concentrations. Abstract: Edaphic aluminum (Al) is toxic to nearly all plant species. Al-accumulating species, however, can accumulate more than 1000 mg Al kg−1 dry leaves without showing toxicity symptoms. The Brazilian savanna, known as ‘Cerrado’, is home to a woody plant community composed of few species from four families of Al-accumulating plants and the rest, non-accumulating ones. The leaves are the target organs when searching for Al roles in these plants, although the roots are the first organ to get in contact with Al. Thus, the roots are being neglected in field studies with accumulating and non-accumulating plants. We expected that Al-accumulating species also accumulate Al in their roots, while non-accumulating ones, that accumulate less than 1000 mg Al kg−1 dry leaves, avoid this metal in their roots. Vochysia tucanorum and Qualea grandiflora (Vochysiaceae) showed more than 1000 mg Al kg−1 dry leaves, and the former accumulated 6.8-times more Al in its leaves than the latter. Xylopia aromatica (Annonaceae) and Caryocar brasiliense (Caryocaraceae) showed approximately 100 mg Al kg−1 dry leaves, being considered non-accumulating species. In the roots, V. tucanorum accumulated 7.8-times more Al than Q. grandiflora, which showed 748 ± 191 mg Al kg−1 dry roots. Xylopia aromatica and C. brasiliense accumulated, approximately, 50 and 250 mg Al kg−1 dry roots, respectively. While Al-accumulating species are tolerant, showing high Al concentration in their leaves and varying concentrations in their roots, non-accumulating species from the Cerrado are ‘avoiders’ and retain low Al concentrations in their roots and leaves.
Keywords: Al3+; Cerrado; Cerrado woody species; Non-accumulating plants